2011
DOI: 10.46989/001c.20594
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Carotenoid Sources on Skin Pigmentation of Goldfish (Carassius auratus)

Abstract: The aim of this study was to investigate the effect of different carotenoid sources on goldfish (Carassius auratus) skin pigmentation. The value of goldfish depends on the intensity of the skin color. In the red variety of goldfish, an orange-red hue is desirable. Juvenile goldfish were fed one of five diets for five months to determine the effects of carotenoids on skin pigmentation, growth, feed efficiency, and survival: (1) astaxanthin (carophyll pink at 75 mg/kg), (2) canthaxanthin (carophyll red at 75 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The increase in pigments in the diet does not always provide changes in productive performance. On evaluating the addition of astaxanthin (75 mg kg −1 diet) compared to canthaxanthin (75 mg kg −1 diet) in goldfish, no differences in performance were observed after 144 days for any of the additives (Yeşilayer et al ., 2011). The addition of 6% Clitoria ternatea to the swordtail diet for 40 days did not significantly influence the weight gain or length of the fish (Julia et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in pigments in the diet does not always provide changes in productive performance. On evaluating the addition of astaxanthin (75 mg kg −1 diet) compared to canthaxanthin (75 mg kg −1 diet) in goldfish, no differences in performance were observed after 144 days for any of the additives (Yeşilayer et al ., 2011). The addition of 6% Clitoria ternatea to the swordtail diet for 40 days did not significantly influence the weight gain or length of the fish (Julia et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation with astaxanthin (80 mg kg −1 ) in the diet of common carp of the Nishikigoi variety promoted an increase in a * and a reduction in L * (Nguyen et al ., 2014). The use of canthaxanthin also provided similar variation in these parameters (Yeşilayer et al ., 2011). However, in the present study, no significant difference was observed for these parameters in the swordtail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar line, Abdollahi et al (2019) reported improved skin pigmentation (especially redness value) in Xiphophorus maculatus-fed carotenoid-enriched Artemia. In other instances, improved redness in important ornamental fishes, viz., Koi carp (Sun et al, 2012), clownfish (Ramamoorthy et al, 2010), Labidochromis caeruleus (Yılmaz & Ergün, 2011), C. auratus (Yeşilayer et al, 2011) and…”
Section: Effect On Skin Colourationmentioning
confidence: 99%
“…In addition, there is increasing consumer awareness about environmental impacts and safety of synthetic pigments. Therefore, natural compounds supplementation containing carotenoid is needed to enhance colour performance (Ebeneezar et al, 2020; Gouveia et al, 1996, 2003; Gupta et al, 2007; Unver & Hamzacebi, 2020; Yeşilayer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%